Metallothionein induction inMytilus edulis exposed to cadmium - Bebianno, Maria João (2020)
The exposure of mussels,Mytilus edulis, collected from Whitsand Bay, southwest England, in August 1988, to sublethal concentrations of cadmium (400µg l−1) for 65 d resulted in the induction of metallothionein (MT) synthesis in the soft tissues. In cadmium-exposed mussels, metallothionein concentrations, measured by differential pulse polarography, increased by a factor of three, from 2 to 3 mg g−1 to a maximum of 9 mg g−1 after 30 d. No significant changes could be detected in controls. Cadmium accumulated in the soft tissues of mussels correlated significantly with metallothionein concentrations and can be described by the relationship: MT (mg g−1)=0.045 Cd (µg g−1)+3.03 (r=0.803,P<0.001). Gel chromatography of heat-treated cytosolic extracts showed that the accumulated cadmium is bound principally to the newly formed metallothioneins. Copper and zinc were also analysed in the whole soft-tissues and in subcellular fractions of cadmium-exposed mussels. Although copper concentrations were not affected by cadmium-exposure, zinc levels were significantly reduced. The results demonstrate that the induction of metallothioneins inM. edulis is a quantifiable biological response to sublethal levels of cadmium exposure.